EFFECT OF ZHYROMOL FEED ADDITIVE ON DAIRY PRODUCTIVITY OF COWS - Shutyak, O.V.; Dimchuk, A.V. (Podilian Bulletin: Agriculture, Engineering, Economics, 2022)
Dry post – spirit refuse, a by-product of ethyl alcohol and bioethanol production, can improve the supply of protein-deficient protein to farm animals. The conducted researches consider the influence of dry post – spirit refuse from corn grain and the feed additive developed on its basis on indicators of milk productivity of cows. With a slight increase in milk yield during the experiment, the feed additive "Zhiromol" in comparison with the dry post – spirit refuse in the diet of dairy cows, provided an increase in fat content by 0.29%, which allowed to obtain an average of 58 g of milk fat per cow. days. It was found that due to the increase in fat milk yield in cows of the experimental group, milk yields in terms of basic fat content exceeded the same indicator of the control group by 9.7% or 1.7 liters of milk with a fat content of 3.4% per day. Thus, the feed additive for dairy cows "Zhiromol", which contains a set of essential vitamins and minerals significantly exceeds the biological value of the dry post – spirit refuse, increases the percentage of fat in milk and, in general, the efficiency of milk production